MODEL PENGEMBANGAN SPIRITUALITAS ANAK USIA DINI MELALUI KEGIATAN SPIRITUAL KEAGAMAAN - Adnan Syah Sitorus; Isna Maulidya (LPPM IAD Probolinggo, 2025)
This study aims to describe the model of spiritual development in early childhood through religious ritual activities in Islamic Early Childhood Education institutions (PIAUD). The research is grounded in the urgency of spiritual development as a fundamental part of holistic child growth, which remains underexplored in the context of Islamic education. A qualitative descriptive approach was employed using a case study method. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed using Miles and Huberman's interactive model. The findings reveal that ritual activities such as daily prayers, dhuha prayer, and collective dhikr serve as effective tools for instilling spiritual values through consistent habituation. Teachers play a central role as moral exemplars (uswah hasanah), while integrated learning enables the infusion of spiritual values into non-ritual activities like storytelling and play. Parental involvement further reinforces the internalization of Islamic values at home. The study concludes that nurturing children's spirituality requires a synergy of habituation, teacher modeling, integrated learning, and family collaboration. Keywords: Spirituality; Early Chilhood; Religious Rituals; Islamic Education